Lunda-Ndembu : Style, Change, and Social Transformation in South Central Africa - Pritchett, James Anthony (Book collections on Project MUSE., 2001)
Pritchett (anthropology, African studies, Boston U.) presents an account of the Lunda- Ndembu people of northwestern Zambia. The text is based upon archaeological data, travel accounts, colonial field reports, and the scholarly studies of others, as well as his own field research conducted intermittently over the course of 14 years. He contends that despite much cultural borrowing in recent decades, the Lunda people have an image of themselves that is essentially unchanged. He also reflects on continuity and change in Africa. Annotation copyrighted by Book News, Inc., Portland, OR.